Marijuana Use Among Young Black Men Who Have Sex With Men and the HIV Care Continuum: Findings From the uConnect Cohort. (9th November 2016) - Morgan, Ethan; Khanna, Aditya S.; Skaathun, Britt; Michaels, Stuart; Young, Lindsay; Duvoisin, Rebeccah; Chang, Ming; Voisin, Dexter; Cornwell, Benjamin; Coombs, Robert W.; Friedman, Samuel R.; Schneider, John A.
ABSTRACT: Background: Young Black men who have sex with men (YBMSM) are at highest risk for HIV seroconversion in the United States. Successful movement through the HIV care continuum is an important intervention for limiting onwards HIV transmission. Objective: Little data exists on how substances most commonly used by YBMSM, such as marijuana, are related to the HIV continuum, which represents the primary aim of this study. Methods: A cohort of YBMSM ( n = 618) was generated through respondent-driven sampling. Frequency of marijuana use and marijuana use as a sex-drug were assessed across the HIV care continuum using weighted logistic regression models. Results: Study participants reported more intermittent marijuana use ( n = 254, 56.2%) compared to heavy use ( n = 198, 43.8%). Our sample contained 212 (34.3%) HIV seropositive participants of which 52 (24.5%) were unaware of their HIV positive status. Study participants who were heavy marijuana users were more likely to be unaware of their HIV seropositive status (AOR: 4.18; 95% CI 1.26, 13.89). All other stages in the care continuum demonstrated no significant differences between those who use marijuana intermittently or heavily or as a sex-drug and nonusers. Conclusions: YBMSM who used marijuana heavily were more likely to be HIV-positive unaware than those who never used marijuana. Findings were inconclusive regarding the relationships between marijuana use and other HIV care continuum metrics. However, knowledge of ones' HIV status is a critical requirement for engaging in care and may have implications for onwards HIV transmission.